Development and Evaluation of the Environment and Communication Assessment Toolkit with Speech-Language Pathologists - Bruce, Carrie; Brush, Jennifer A.; Sanford, Jon A.; Calkins, Margaret P. (Seminars in Speech and Language, 2013)
Communication dysfunction that results from dementia can be exacerbated by environmental barriers such as inadequate lighting, noisy conditions, poor or absent environmental cues, and visual clutter. Speech-language pathologists (SLPs) should address these environmental barriers as part of a comprehensive treatment plan for clients with dementia. The Environment and Communication Assessment Toolkit for Dementia Care (ECAT) was evaluated by SLPs to determine: (1) changes in awareness of environmental factors prior to and after training; (2) impact of the ECAT on practice as measured by changes in the number of environmental modifications recommended and made prior to and after training; (3) utility of the information as measured by the helpfulness, amount of new information, and usefulness of the ECAT; and (4) usability of the ECAT materials based on ease of use. The SLPs used the ECAT with clients with dementia who had functional limitations and required substantial assistance with daily activities. Results indicate that the ECAT is an effective tool for SLPs, providing information about the impact of the environment on communication and supplying sufficient resources to make recommendations and implement effective interventions. The ECAT successfully increased awareness of environmental modifications, influenced the practice of recommending environmental modifications, and had utility in diverse aspects of clinical practice.
Keywords: Dementia; environmental modifications; communication environment; environmental interventions